Peran Pemerintah dalam Pengembangan Industri Halal - Erna Indriastiningsih; Parmini; Mustofa As'ady; Retnawati Siregar; Asri Ady Bakri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this study is to determine the role of government in the development of the halal industry. This research approach collects data through literature studies, which involve reading literature from various sources including books, journals and reports using qualitative and deductive approaches. The findings in this study are that the government plays a very important role in the development of the halal industry. The strategies used in the development of the halal industry include strengthening the halal value chain, strengthening Islamic finance, strengthening the MSME sector, strengthening the digital economy, strengthening halal industry management, and strengthening halal product certification. In addition, there are five moves used by the government as the key to making Indonesia a global halal industry production base, including competitiveness (competitiveness), certification (certification), coordination (coordination), campaign (campaign), and cooperation (cooperation).